Spatially Resolved Operando Synchrotron-Based X-Ray Diffraction Measurements of Ni-Rich Cathodes for Li-Ion Batteries - Leach, Andrew Stephen; Llewellyn, Alice V.; Xu, Chao; Tan, Chun; Heenan, Thomas M. M.; Dimitrijevic, Alex; Kleiner, Karin; Grey, Clare P.; Brett, Dan J. L.; Tang, Chiu C.; Shearing, Paul R.; Jervis, Rhodri (Frontiers in Chemical Engineering, 2022)
Understanding the performance of commercially relevant cathode materials for lithium-ion (Li-ion) batteries is vital to realise the potential of high-capacity materials for automotive applications. Of particular interest is the spatial variation of crystallographic behaviour across (what can be) highly inhomogeneous electrodes. In this work, a high-resolution X-ray diffraction technique was used to obtain operando transmission measurements of Li-ion pouch cells to measure the spatial variances in the cell during electrochemical cycling. Through spatially resolved investigations of the crystallographic structures, the distribution of states of charge has been elucidated. A larger portion of the charging is accounted for by the central parts, with the edges and corners delithiating to a lesser extent for a given average electrode voltage. The cells were cycled to different upper cut-off voltages (4.2 and 4.3 V vs graphite) and C-rates (0.5C, 1C and 3C) to study the effect on the structure of the NMC811 cathode. By combining this rapid data collection method with a detailed Rietveld refinement of degraded NMC811, the spatial dependence of the degradation caused by long term cycling (900 cycles) has also been shown. The variance shown in the pristine measurements is exaggerated in the aged cells with the edges and corners offering an even lower percentage of the charge. Measurements collected at the very edge of the cell have also highlighted the importance of electrode alignment, with a misalignment of less than 0.5 mm leading to significantly reduced electrochemical activity in that area.